Strategi Penanggulangan Pelanggaran Lalu Lintas Terhadap Remaja (Studi pada Satlantas Polresta Banda Aceh) - T Syarifuddin; Rania Endah Lestari (Journal of Social and Policy Issues, 2022)
This study aims to determine the efforts and obstacles of the Banda Aceh Resort Police Traffic Unit in tackling Traffic Violations by Teenagers as Motorcyclists. This research uses qualitative methods. Data sources are obtained through methods of observation, interviews, and documentation. The data inspection technique uses the triangulation technique method. The results of the study are known that the efforts of the Banda Aceh Resort Police Traffic Unit in tackling traffic violations committed by teenagers as motorcyclists, preventive actions, namely collaborating with several schools in Banda Aceh City to educate students not to do dangerous things using their motorcycles, either by violating traffic rules or by modifying motorcycles that can interfere with the driving comfort of others. Repressive efforts are carried out with raids to regulate traffic violations, to provide education and a deterrent effect so that teenagers who are not old enough to ride motorcycles do not use motorcycles on the road. The obstacles of the Banda Aceh Resort Police Traffic Unit in tackling Traffic Violations by Teenagers as Motorcyclists are, Neglected by parents has led to an increase in the phenomenon of school students using motorcycles even though they are not yet 17 years old. Research advises it is hoped that parents can provide understanding to their teens not to use motorcycles on the road because of the risk of accidents and crossings by the police for violating traffic rules